Water Model Experiments on the Influence of Phase Distribution in the Submerged Entry Nozzle Considering Varying Operating Conditions. Issue 12 (14th July 2022) - Thumfart, Maria; Hackl, Gernot; Fellner, Wolfgang
Abstract : Continuous casting of steel argon injection into the submerged entry nozzle (SEN) via the stopper is common practice. Nonetheless, the resulting phase distribution in the SEN is still under discussion. The main available casting parameters at the steel plant to determine the flow situation in the SEN are usually the stopper rod position, the argon feeding pressure, the argon flow rate, and the casting speed. To show the potential influence of the phase distribution on the stopper characteristic and on the argon feeding pressure, experiments using a 1:3 scale water model are presented. For the experiment, the water flow rate is scaled using Froude similarity, while the air flow rate is chosen to keep the ratio between the liquid and gas volume flow rate constant. The casting parameters and the pressure at three distinct levels of the SEN are measured. To relate this measurement data to the corresponding phase distribution, two cameras are used to document the phase distribution in the SEN. The images show four major phase distribution patterns. These patterns can be linked to significant changes in the measured pressure levels and the behavior of the stopper. Abstract : The experimental data of a 1:3 water model of a continuous caster presented herein show the strong influence of phase distribution in the submerged entry nozzle (SEN) on the pressure distribution in the SEN and on the stopper position. These findings are based on the influence of the wetting conditions of the SEN walls and on a hysteresis effect.